2013
DOI: 10.1177/0194599813505972
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Otolaryngology Services in Central America: Need for a Comprehensive Intervention

Abstract: In the developing world, there exists a scarcity of services and training in otolaryngology, audiology, and speech therapy, which is reflected by the gap between health care delivery in high-income countries and low-income countries. We surveyed, by questionnaire, the countries of Central America, except for Belize, because of the lack of otolaryngology services, on the following issues: availability of otolaryngology, audiology, and speech therapy services and equipment; otolaryngologist, audiologist, and spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 4 publications
1
25
0
Order By: Relevance
“…30,32 Patients are often misdiagnosed as having asthma, laryngotracheobronchitis, foreign body aspiration or laryngomalacia. 3 In developing countries, as a result of the poor availability of healthcare services in general and ENT services in particular, [42][43][44] patients frequently present with upper airway obstruction and a history of hoarseness for many years. 3,4,30,40,41,[45][46][47][48][49][50][51] In a South African study, all patients diagnosed in the private sector had only hoarseness on initial presentation, while 70.1% of patients diagnosed in the public sector also presented with stridor, with 51.9% being in respiratory distress.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…30,32 Patients are often misdiagnosed as having asthma, laryngotracheobronchitis, foreign body aspiration or laryngomalacia. 3 In developing countries, as a result of the poor availability of healthcare services in general and ENT services in particular, [42][43][44] patients frequently present with upper airway obstruction and a history of hoarseness for many years. 3,4,30,40,41,[45][46][47][48][49][50][51] In a South African study, all patients diagnosed in the private sector had only hoarseness on initial presentation, while 70.1% of patients diagnosed in the public sector also presented with stridor, with 51.9% being in respiratory distress.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…75,92 While formal voice evaluation and therapy may be of value in the management of patients, 56 these services are often not available in developing countries. [42][43][44]…”
Section: Speech Therapymentioning
confidence: 99%
“…[6][7][8][9] This situation of ENT diseases gets further complexed by the fact that, as there are only a few population-based epidemiological studies on ENT psycho-social assessments among adults. 10,11 Although many studies have explored the physical needs of ENT patients from pediatric age group to elderly in Primary health care to tertiary health care set ups across the world. [6][7][8][9][10][11][12][13][14][15][16] Such kind of studies have also shown that, they can help in effective treatment prioritization of ear, nose, throat disorders with an added advantage in planning and resource allocation, which is relevant in Indian context due to the presence of higher prevalence of otorhinolaryngological morbidities and scarce resources.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Although many studies have explored the physical needs of ENT patients from pediatric age group to elderly in Primary health care to tertiary health care set ups across the world. [6][7][8][9][10][11][12][13][14][15][16] Such kind of studies have also shown that, they can help in effective treatment prioritization of ear, nose, throat disorders with an added advantage in planning and resource allocation, which is relevant in Indian context due to the presence of higher prevalence of otorhinolaryngological morbidities and scarce resources. [6][7][8][9][10][11][12][13][14][15][16][17] It has also been seen from studies that even the most common ENT disorders presenting to the emergency department can be tackled at the level of primary health care level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation